Beyond slash and burn: a searching look at Uma’ jalan forest knowledge - Colfer, C.J.P. (1995)
In this chapter, it discusses the way the Uma’ Jalan Kenyah of East Kalimantan view their agroforestry system. The Uma’ Jalan do not make the strict division that we do between “agriculture” and “forestry.” For ease of explanation, however, it first describes their view of ricefields, home gardens, and gardens. Then turns to a forestry perspective, with an introduction to their knowledge of rainforest products. Further it looks specifically at the kinds of products which they tend and/or harvest in four stages of forest re-growth after rice cultivation: bekan (new fallow), jekau bu’et (young secondary regrowth), jekau dado’ (old secondary rgrowth) and mpa’ (old growth). It concludes with policy recommendations based on these findings.